2004
DOI: 10.1177/0091270004267594
|View full text |Cite
|
Sign up to set email alerts
|

Ibandronate: A Clinical Pharmacological and Pharmacokinetic Update

Abstract: Ibandronate is a potent nitrogen-containing bisphosphonate. It has a strong affinity for bone mineral and potently inhibits osteoclast-mediated bone resorption. Ibandronate is effective for the treatment of hypercalcemia of malignancy, metastatic bone disease, postmenopausal osteoporosis, corticosteroid-induced osteoporosis, and Paget's disease. Oral ibandronate is rapidly absorbed (t(max) < 1 hour), with a low bioavailability (0.63%) that is further reduced (by up to 90%) in the presence of food. Ibandronate … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

12
124
1
13

Year Published

2007
2007
2013
2013

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 135 publications
(150 citation statements)
references
References 89 publications
(133 reference statements)
12
124
1
13
Order By: Relevance
“…These in vitro findings are in line with the available data reported for other bisphosphonates: for alendronate, plasma protein binding in the rat is higher than in dog and human , and alendronate and etidronate show a concentration dependence of plasma protein bind-ing (Lin, 1996). The renal clearance of zoledronic acid, 60 ml/min (Skerjanec et al, 2003), is identical to that reported for ibandronate (Barrett et al, 2004), consistent with our finding of comparable plasma protein binding of the two drugs.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…These in vitro findings are in line with the available data reported for other bisphosphonates: for alendronate, plasma protein binding in the rat is higher than in dog and human , and alendronate and etidronate show a concentration dependence of plasma protein bind-ing (Lin, 1996). The renal clearance of zoledronic acid, 60 ml/min (Skerjanec et al, 2003), is identical to that reported for ibandronate (Barrett et al, 2004), consistent with our finding of comparable plasma protein binding of the two drugs.…”
Section: Discussionsupporting
confidence: 92%
“…Plasma protein binding of zoledronic acid was observed to be dependent on plasma free calcium levels and pH, as has been reported previously for alendronate (Lin et al, 1993;Lin, 1996). Slight shifts in the pH of plasma during in vitro incubations (e.g., due to loss of carbon dioxide) may contribute, together with other factors, to interstudy variability of plasma protein binding, possibly leading to the wide differences in reported values for ibandronate (Barrett et al, 2004;Dooley and Balfour, 1999). Under rigorous testing conditions, the protein binding of ibandronate in human plasma was found to be slightly lower than that of zoledronic acid.…”
Section: Discussionsupporting
confidence: 74%
“…Bisphosphonates inhibit bone resorption as shown by decreased serum bone turnover markers of bone type I collagen degradation [18]. Ibandronate, a potent nitrogen-containing bisphosphonate with affinity for hydroxyapatite [19], inhibits osteoclast-mediated bone resorption and is effective in the treatment of estrogen-deficient osteoporosis. Its high in vivo potency prevents estrogen-dependent bone loss and it improves bone mass, bone strength and bone architectural parameters in rats [20][21][22].…”
Section: Introductionmentioning
confidence: 99%
“…ibandronate was administered to humans or animals. 17 Even at concentrations greater than 1000-fold than those found clinically, there is a lack of affinity between ibandronate and the major cytochrome P450 isoforms. Metabolic stability and urinary excretion of the unchanged compound are characteristics associated with all bisphosphonates.…”
mentioning
confidence: 99%
“…[13][14][15][16] The pharmacokinetic profile of ibandronate has previously been described in detail by Barrett and colleagues. 17 Therefore, presented here is an overview of the key points.…”
mentioning
confidence: 99%